PENGARUH KEPUASAN KERJA, MOTIVASI KERJA DAN GAYA KEPEMIMPINAN TERHADAP KINERJA KARYAWAN HOTEL GRAND ORCHID DI SOLO - -, Sinangdoyo (JURNAL MANAJEMEN SUMBER DAYA MANUSIA, 2015)
The aim of this research are to determine effect of job satisfaction on performance of Grand Orchid Hotel’s employees in Solo City, effect of motivation on performance of Grand Orchid Hotel’s employees in Solo City, effect of leadership on performance of Grand Orchid Hotel’s employees in Solo City, and among these variables which its effect on performance of Grand Orchid Hotel’s employees in Solo City is dominant. This research is a quantitative with 74 respondents of an entire population of Grand Orchid Hotel and using questionnaire method for data collection. Data analysis which used is multiple linear regression. The result of this research are job satisfaction has positive influence on performance of Grand Orchid Hotel’s employees in Solo City, motivation has positive influence on performance of Grand Orchid Hotel’s employees in Solo City, leadership has positive influence on performance of Grand Orchid Hotel’s employees in Solo City. Among the used variables, the most dominant variable which have an influence on performance of Grand Orchid Hotel’s employees in Solo City is leadership because it has the greater coefficient, is 0,348. These three variables contribute 43,9 percent on performance of Grand Orchid Hotel’s employees in Solo City. Keywords: job satisfaction, motivation, leadership, performance.